Excel 2013 for Health Services Management Statistics A Guide to Solving Practical Problems - Quirk, Thomas J.; Cummings, Simone (Excel for Statistics, 2016)
This book shows the capabilities of Microsoft Excel to teach health services management statistics effectively. Similar to the previously published Excel 2010 for Health Services Management Statistics, this book is a step-by-step exercise-driven guide for students and practitioners who need to master Excel to solve practical health services management problems. If understanding statistics isn't your strongest suit, you are not especially mathematically-inclined, or if you are wary of computers, this is the right book for you. Excel, a widely available computer program for students and managers, is also an effective teaching and learning tool for quantitative analyses in health services management courses. Its powerful computational ability and graphical functions make learning statistics much easier than in years past. However, Excel 2013 for Health Services Management Statistics: A Guide to Solving Practical Problems is the first book to capitalize on these improvements by teaching students and managers how to apply Excel to statistical techniques necessary in their courses and work. Each chapter explains statistical formulas and directs the reader to use Excel commands to solve specific, easy-to-understand health services management problems. Practice problems are provided at the end of each chapter with their solutions in an Appendix. Separately, there is a full Practice Test (with answers in an Appendix) that allows readers to test what they have learned. n Includes 163 illustrations in color n Suitable for undergraduate and graduate students At the beginning of his academic career, Prof. Quirk spent six years in educational research at The American Institutes for Research and Educational Testing Service. He is currently a Professor of Marketing in the Walker School of Business & Technology at Webster University based in St. Louis, Missouri (USA). He holds a B.S. in Mathematics from John Carroll University, both an M.A. in Education and a Ph.D. in Educational Psychology from Stanford University, and an MBA from The University of Missouri-St. Louis. Prof. Cummings has worked for several hospitals in St. Louis, Missouri, and Washington, D.C. She is currently an Associate Professor of Healthcare Management in the Walker School of Business & Technology at Webster University in St. Louis, Missouri (USA) where she teaches Statistics for Healthcare Management and Healthcare Finance. She holds a B.S.B.A. from Washington University in St. Louis, an M.H.A. from the Washington University School of Medicine, and a Ph.D. in Health Policy and Administration from the University of North Carolina Chapel Hill. .